2016
DOI: 10.18857/jkpt.2016.28.5.321
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Items of Functioning Questionnaires into the International Classification of Functioning, Disability and Health: Low Back Pain

Abstract: Purpose:The purpose was to link items of questionnaires that measure functioning and disability of persons with Low Back Pain (LBP) into the International Classification of Functioning, Disability and Health (ICF). Methods: The Oswestry Disability Index (ODI), Roland and Morris Disability Questionnaire (RM), Fear-Avoidance Beliefs Questionnaire (FABQ), and Short Form-36 health survey (SF-36) were evaluated to map items of those questionnaires into the ICF categories. The linking rule was employed and linking w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The ODI scores are divided into 0-20% (minimal disability), 21-40% (moderate disability), 40-60% (severe disability), and 60% or above (severely disabled life). 10 It is usable in a wide variety of applications as a condition-specific outcome measure of spine-related disability.…”
Section: -9mentioning
confidence: 99%
“…The ODI scores are divided into 0-20% (minimal disability), 21-40% (moderate disability), 40-60% (severe disability), and 60% or above (severely disabled life). 10 It is usable in a wide variety of applications as a condition-specific outcome measure of spine-related disability.…”
Section: -9mentioning
confidence: 99%
“…In clinical measurement tools, it was often observed that one concept was present in several items with different ranges of intensity or frequency, and each of those items could be linked to one ICF code. 15,16 This study showed that the level of performing certain activities was included in sequential items in both DASH and SF-36, such as carrying light object (item 10), carrying heavy object (item 11) in DASH, and climbing from one flight (item 6) to several flights of stairs (item 7) in SF-36. The concept related to executing the activity is the same in those items and, therefore, they could be linked to one ICF category (d430 lifting and carrying objects, d4551 climbing, respectively) whereas the intensity or extent of activities was not directly linked to ICF codes, as intensity of some activities is not included within ICF.…”
Section: Discussionmentioning
confidence: 96%
“…This could indicate differences between specific and generic tools. 15,16 Dressing (item 12) was included in SF-36, whereas putting on a pullover sweater (item 15) was in DASH, and those items were linked to dressing (d540) and putting on clothes (d5400), respectively. Other items, such as bathing (item 12) in SF-36 vs. washing one's back (item 14) and wash or dry hair (item 13) in DASH were linked to washing (d510), washing body parts (d5100), and drying oneself (d5102), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Functioning measurement tools have been linked to ICF to promote communications among relevant professionals in Korea. 5,8 WHODAS II was published in 2004 based on the WHO psychiatric disability assessment schedule which was designated to assess the extent of disability associated with a psychiatric condition.…”
Section: Introductionmentioning
confidence: 99%